CAR-T therapy for endocrine neoplasms: novel targets and combination of therapies - Wang, Fang; Zhang, Ruiqi; Zhou, Zhaokai; Shi, Run; Peng, Fu; Xu, Yudi; Yang, Shuai; Wang, Zhan; Zhang, Pengpeng; Tu, Rui; Zhang, Chun; Liu, Xingchen; et al. (Frontiers in Endocrinology, 2025)
Endocrine malignancies constitute a heterogeneous tumour group with diverse biological characteristics. While typically indolent, they encompass aggressive types and presence of any metastatic sign indicates a high probability of recurrence and a diminished response to conventional therapies. Chimeric antigen receptor (CAR)-T cell immunotherapy has constituted a revolutionary advance in cancer treatment and exhibited significant potential for application in endocrine cancer. However, limited effectiveness was displayed in clinical application, which necessitates the exploration of novel modalities. Identification of specific and safe targets for endocrine cancer is the initial stage towards establishing a successful CAR-T treatment. Various therapies under investigation offer potential enhancements to CAR T cell efficacy through diverse mechanisms. Herein, we summarize recent advances in identifying targets of endocrine cancer for CAR therapy and provide an overview of combinatorial approaches.